Kajian Etnosains Silek Kumango Minangkabau: Identifikasi Konsep Fisika dan Biologi sebagai Potensi Sumber Belajar di SMA - Dian Purnama Ilahi; Arista Ratih (PendIPA Journal of Science Education, 2026)
The teaching of physics and biology as part of science education in high school should be linked to real-world phenomena and local culture so that students can understand scientific concepts in context. One aspect of Minangkabau culture that has the potential to serve as a learning resource in high school is Silek Kumango, a style of silek originating from Nagari Kumango, Tanah Datar, West Sumatra. This study aims to examine Minangkabau Silek Kumango through an ethoscience approach by identifying the physics and biology concepts present in its movements as a potential learning resource for high school students. The method used is a descriptive qualitative approach based on a literature review. Data were collected from scientific articles, documents, and previous research findings regarding Silek Kumango, ethnoscience, and culture-based science education. The findings indicate that Silek Kumango incorporates physics concepts such as motion, force, equilibrium, impulse, momentum, work, energy, torque, center of mass, and friction. From a biological perspective, Silek Kumango relates to the human musculoskeletal system, muscle function, joints, neural coordination, body balance, reflex responses, respiration, and physical fitness. The integration of Silek Kumango into high school physics and biology instruction can serve as a contextual learning resource for topics such as motion, energy, the human musculoskeletal system, the nervous system, the respiratory system, and the circulatory system. This study demonstrates that local culture functions not only as a cultural heritage but also as a bridge between community knowledge and scientific knowledge in schools.